The relationship between compliance in the treatment of pulmonary TB to lung function in Humbang Hasundutan district - Risma Dumiri Manurung (Universitas Aisyah Pringsewu, 2023)
Pulmonary TB is one of the ten causes of death and the main cause of infectious agents. Pulmonary TB germs that occur due to splashes of saliva when talking, sneezing, or coughing are related to behavior and closest contacts, for example a family living in the same household is twice as likely to be at risk than regular contact or not living in the same house. Prevention _it becomes very important to break the chain of transmission by knowing the factors that influence pulmonary TB disease. Pulmonary TB treatment which takes 6-8 months often causes drug withdrawal which can lead to resistance to Anti Tuberculosis Drugs (OAT). This study aims to determine the effect of compliance with pulmonary TB patients in treatment on lung function of respondents in Humbang Hasundutan District. This type of quasi-experimental research with a cross-sectional research design. The study population of pulmonary TB patients was 60 people. Sampling by purposive sampling. Univariate and bivariate data analysis with Test Chi Square CI 95% a less than 0.05. The results of the study based on the characteristics of the majority of respondents aged at intervals more than 35 years were 43 respondents (71.7%), with a gender majority 45 respondents (75%) were male, 39 respondents (65%) were in high school, the majority of respondents were engaged in farming, 44 respondents were employed (73, 3%) and for income majority at intervals of 1 million to 3 million as many as 36 respondents (60%). 54 people (90%) comply, and 45 people (75%) have adequate lung function. The chi-square test showed that compliance with respondents in pulmonary TB therapy affect lung function with a p-value of 0.003 (p 0.05).